Clinical and radiographic predictors of the need for facial CT in pediatric blunt trauma: a multi-institutional study. Issue 1 (25th April 2022) - Nguyen, Brittany N; Edwards, Mary J; Srivatsa, Shachi; Wakeman, Derek; Calderon, Thais; Lamoshi, Abdularouf; Wallenstein, Kim; Fabiano, Tiffany; Cantor, Brittany; Bass, Kathryn; Narayan, Ananth; Zohn, Ralph; et al.
Abstract : Background: Facial injuries are common in children with blunt trauma. Most are soft tissue lacerations and dental injuries readily apparent on clinical examination. Fractures requiring operative intervention are rare. Guidelines for utilization of maxillofacial CT in children are lacking. We hypothesized that head CT is a useful screening tool to identify children requiring dedicated facial CT. Methods: We conducted a multicenter retrospective review of children aged 18 years and under with blunt facial injury who underwent both CT of the face and head from 2014 through 2018 at five pediatric trauma centers. Penetrating injuries and animal bites were excluded. Imaging and physical examination findings as well as interventions for facial fracture were reviewed. Clinically significant fractures were those requiring an intervention during hospital stay or within 30 days of injury. Results: 322 children with facial fractures were identified. Head CT was able to identify a facial fracture in 89% (287 of 322) of children with facial fractures seen on dedicated facial CT. Minimally displaced nasal fractures, mandibular fractures, and dental injuries were the most common facial fractures not identified on head CT. Only 2% of the cohort (7 of 322) had facial injuries missed on head CT and required an intervention. All seven had mandibular or alveolar plate injuries with findings on physical examination suggestive of injury. Discussion: In pediatric blunt trauma, head CT is an excellent screening tool for facial fracture. In the absence of clinical evidence of a mandibular or dental injury, a normal head CT will usually exclude a clinically significant facial fracture. Level of evidence: III.